Analysis of INSPPIRE-2 Cohort: Risk Factors and Disease Burden in Children With Acute Recurrent or Chronic Pancreatitis. Issue 5 (17th August 2022) - Uc, Aliye; Cress, Gretchen A.; Wang, Fuchenchu; Abu-El-Haija, Maisam; Ellery, Kate M.; Fishman, Douglas S.; Gariepy, Cheryl E.; Gonska, Tanja; Lin, Tom K.; Liu, Quin Y.; Mehta, Megha; Maqbool, Asim; et al.
Abstract : Objectives: The objective of this study is to investigate risk factors and disease burden in pediatric acute recurrent pancreatitis (ARP) and chronic pancreatitis (CP). Methods: Data were obtained from INternational Study group of Pediatric Pancreatitis: In search for a cuRE-2 (INSPPIRE-2), the largest multi-center prospective cohort study in pediatric patients with ARP or CP. Results: Of 689 children, 365 had ARP (53%), 324 had CP (47%). CP was more commonly associated with female sex, younger age at first acute pancreatitis (AP) attack, Asian race, family history of CP, lower BMI%, genetic and obstructive factors, PRSS1 mutations and pancreas divisum. CFTR mutations, toxic-metabolic factors, medication use, hypertriglyceridemia, Crohn disease were more common in children with ARP. Constant or frequent abdominal pain, emergency room (ER) visits, hospitalizations, medical, endoscopic or surgical therapies were significantly more common in CP, episodic pain in ARP. A total of 33.1% of children with CP had exocrine pancreatic insufficiency (EPI), 8.7% had diabetes mellitus. Compared to boys, girls were more likely to report pain impacting socialization and school, medical therapies, cholecystectomy, but no increased opioid use. There was no difference in race, ethnicity, age at first AP episode, age at CP diagnosis, duration of disease, risk factors, prevalence of EPI or diabetes between boys and girls. Multivariate analysis revealed that family history of CP, constant pain, obstructive risk factors were predictors of CP. Conclusions: Children with family history of CP, constant pain, or obstructive risk factors should raise suspicion for CP.